2018
DOI: 10.1111/adb.12634
|View full text |Cite
|
Sign up to set email alerts
|

Preventing morphine reinforcement with high‐frequency deep brain stimulation of the lateral hypothalamic area

Abstract: Deep brain stimulation (DBS) has been proposed as a promising intervention for patients with treatment-refractory substance use disorder. Here, we investigated if high-frequency DBS in the lateral hypothalamic area (LHA) could affect drug-induced reinforcement. Rats were bilaterally implanted with bipolar stimulation electrodes in the LHA and trained to the morphine conditioned place preference. DBS (monophasic square pulses, 130 Hz, 100-microsecond pulse duration and 150 μA) was applied during the morphine-pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 45 publications
0
13
0
Order By: Relevance
“…In the present study, we did not observe any change in locomotor activity by DBS. In addition, our previous study showed that LH DBS did not affect locomotor activity, anxiety level, body weight, and sucrose reward (8). But it should be noted that we applied DBS for a very short duration of time (20 min/day for nine days; or 40 min/day for four days in the previous study) that might not be enough to cause the likely complications.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…In the present study, we did not observe any change in locomotor activity by DBS. In addition, our previous study showed that LH DBS did not affect locomotor activity, anxiety level, body weight, and sucrose reward (8). But it should be noted that we applied DBS for a very short duration of time (20 min/day for nine days; or 40 min/day for four days in the previous study) that might not be enough to cause the likely complications.…”
Section: Discussionmentioning
confidence: 97%
“…Another study reported mostly negative results by showing that HF‐DBS of the MFB at the LH did not block amphetamine effect to reduce the threshold for ICSS, whereas it markedly augmented the effect of haloperidol to suppress ICSS reward (10). In our previous study, we have shown that HF‐DBS of the LH during the conditioning trials abolished acquisition of morphine place preference, though it did not affect sucrose consumption as a natural reward (8). Here, we extended previous findings by showing that HF‐DBS of the LH over the extinction phase facilitated the active inhibition of morphine place preference.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…19 Our previous study also showed that DBS-like stimulation of the lateral hypothalamic area blocked morphine reinforcement in rats. 20 Additionally, DBS of the NAc proved effective in reducing subjective craving and abstaining from heroin consumption in a number of therapy-resistant opioidaddicted patients. [21][22][23] Considering the involvement of the OFC in addictive behaviors and the promising results from DBS application in preclinical and clinical studies of addiction, in the present study, we investigated the potential efficacy of DBS in the OFC for controlling addictive-like behaviors in rats.…”
Section: Deep Brain Stimulation (Dbs)mentioning
confidence: 99%
“…The DBS commonly utilizes sequences of narrow pulses with a pulse width around 0.1 ms and a pulse frequency ~ 100-200 Hz (termed as high-frequency stimulation, HFS). Charge-balanced biphasic pulses (with a preceding negative pulse immediately followed by a positive one) are usually utilized in clinical DBS for safety [3,4], while negative monophasic pulses are used in animal studies for investigating DBS therapy [5][6][7].…”
Section: Introductionmentioning
confidence: 99%